Determination of proximate composition of Malaysian horseshoe crab (Tachypleus gigas) - Nashrin Iszhan, Ishak; Nazikussabah, Zaharudin; Farah Nurshahida, Mohd Subakir (Scientific.Net, 2021)
This study was conducted to investigate proximate content of horseshoe crab (Tachypleus gigas) in Malaysia. To date, there has been little agreement on what the nutrition value of horseshoe crab is and how it will benefit the consumers. The samples were divided by two parts, which are roe and muscle. The Tachypleus gigas was cleaned of foreign materials and impurities manually by human hand. The samples were ground into flour and sieved through 50 μm sieve and were packaged in airtight plastic bags prior to analyses. The horseshoe crab was analyzed for its proximate composition of different body parts. The results showed that the roe and muscle of Tachypleus gigas contained moisture (50.45 % and 73.67 %), ash (0.41 % and 2.72 %), crude proteins (38.24 % and 14.62 %), crude fats (9.30 % and 8.09 %), carbohydrates (1.67 % and 0.91 %) and energy (241.42 Kcal/100 g and 134.43 Kcal/100 g), respectively. This shows that roe has better nutrition content since it has higher protein, fat and carbohydrate content, which are the main energy-providing nutrient. Overall, the proximate content of Tachypleus gigas was nearer to the shellfish rather than the finfish and can be considered as a good nutrition source.